Agro-economic Feasibility and Indices of Castor+Groundnut Intercropping System Under Irrigated Conditions During Rabi Season in Telangana - Ramanjaneyulu, A. V.; Reddy, K. Indudhar; Kumar, M. V. Nagesh; Madhavi, A.; Ramana, M. Venkata; Srinivas, A.; Suresh, G. (International Journal of Bio-resource and Stress Management, 2021)
An experiment was carried out for three consecutive years from 2014-15 to 2016-17 at Regional Agricultural Research Station (RARS), Palem, Professor Jayashankar Telangana State Agricultural University, Telangana, India to study and understand the agro-economic feasibility and various indices of castor+groundnut intercropping system under irrigated conditions during rabi season. There were six treatments viz., sole castor, sole groundnut, castor+groundnut (1:5) with RDF (recommended dose of fertilizer) to both the crops, castor+groundnut (1:7) with RDF to both the crops, castor+groundnut (1:5) with RDF to castor alone and castor+groundnut (1:7) with RDF to castor alone. The results indicated that sole groundnut with significantly higher castor equivalent yield (3960 kg ha-1) gave a higher yield advantage by 12.5 to 25.8% over castor+groundnut intercropping and 102.5% over sole castor. Further, sole groundnut recorded higher water use efficiency (10.25 kg ha-1 mm-1) and net returns per mm water used (Rs. 243.65 mm-1). The economics also indicated that sole groundnut was profitable in terms of gross (Rs. 1,50,465 ha-1) and net returns (Rs. 94,150 ha-1). However, higher benefit:cost ratio was observed with sole castor (2.76) followed by sole groundnut (2.67) and castor+groundnut intercropping (1:5) with RDF applied to both crops (2.57). Among various indices, the highest land equivalent ratio (1.13), area time equivalency ratio (1.00) and monetary advantage index (15072) were recorded with castor+groundnut (1:5) where RDF was applied to both the crops.